Donor acceptor fluorophores: synthesis, optical properties, TD-DFT and cytotoxicity studies. Issue 8 (10th February 2021) - Essam, Zahraa M.; Ozmen, Guliz Ersoy; Setiawan, Dani; Hamid, Riri Rizkianty; Abd El-Aal, Reda M.; Aneja, Ritu; Hamelberg, Donald; Henary, Maged
Abstract : We report a series of NIR D–A fluorophores with a cyanoacrylic acid acceptor and various donor units. The cytotoxicity of selected fluorophores against triple negative breast cancer cell lines showed stronger activity than that of anticancer agent docetaxel. Abstract : Donor–π-acceptor (D–π-A) fluorophores consisting of a donor unit, a π linker, and an acceptor moiety have attracted attention in the last decade. In this study, we report the synthesis, characterization, optical properties, TD-DFT, and cytotoxicity studies of 17 near infrared (NIR) D–π-A analogs which have not been reported so far to the best of our knowledge. These fluorophores have chloroacrylic acid as the acceptor unit and various donor units such as indole, benzothiazole, benzo[ e ]indole, and quinoline. The fluorophores showed strong absorption in the NIR (700–970 nm) region due to their enhanced intramolecular charge transfer (ICT) between chloroacrylic acid and the donor moieties connected with the Vilsmeier–Haack linker. The emission wavelength maxima of the fluorophores were in between 798 and 870 nm. Compound 20 with a 4-quinoline donor moiety showed an emission wavelength above 1000 nm in the NIR II window. The synthesized fluorophores were characterized by 1 H NMR and 13 C NMR, and their optical properties were studied. Time dependent density functional theory (TD-DFT) calculations showed that the charge transfer occurs from the donor groups (indole, benzothiazole, benzo[ e ]indole, and quinoline) to the acceptor chloroacrylic acid moiety. Fluorophores with [HOMO] to [LUMO+1] transitions were shown to possess a charge separation character. The cytotoxicity of selected fluorophores, 4, 7, 10 and 12 was investigated against breast cancer cell lines and they showed better activity than the anti-cancer agent docetaxel.